Hubungan Kreativitas Guru dengan Kemampuan Berpikir Kritis pada Mata Pelajaran Matematika Siswa Kelas IV - Andi Halvina; Muh Idris Jafar; Mujahidah Mujahidah (Jurnal Pendidikan dan Pembelajaran Sekolah Dasar (JPPSD), 2022)
This research is a correlational quantitative research which to find the description of teacher creativity and the description of students critical thinking skills. Then determine whether or not there is a relationship between teacher creativity and critical thinking skills in the fourth grade mathematics subject at SD Inpres 12/79 Jeppe'e. The population of this study are 44 students. The research instruments used were questionnaires and tests. The data analysis technique was carried out by descriptive analysis and inferential analysis to determine the relationship between the teacher's creativity and the student's critical thinking. The results of the research on teacher creativity and students' critical thinking skills in Mathematics are in good category. Then based on the results of inferential analysis the value (0.533) is greater than the value (0.291) at a significant level of 5%. The results that there is a relationship between teacher creativity and critical thinking skills in Mathematics.